The Influence of Person-Job Fit Toward Job Satisfaction, Organizational Commitment, and Organizational Citizenship Behavior - Rizky Fauzan (Universitas Syiah Kuala, 2023)
: An organization will have human resource management as the central factor which is can be useful to do, manage, and reach the vision and mission that already set by the organization. The quality of the employee is one of the key that can determine improvement of an organization. The success of development program that implemented by the government is depend on the quality and quantity of the human resources that the government have and the management of the human resource ih the company can be review from the organizational behavior that happen in the organization. The purpose of this study is to analyze the impact of Person-Job Fit toward Job Satisfaction, Organizational Commitment, and Organizational Citizenship Behavior in Marine Fisheries Agency and Provincial Inspectorate Agency in West Borneo. The number of population in this research are 180 people, and the sampling technique that used in this research is using the 10 times formative indicator, there are 15 formative indicators so there are 150 samples. The data collection technique that used in this research is by using questionnaire, and the data obtained by distributing the questionnaire to both of the Agencies and the data is evaluated by Structural Equation Model (SEM) and to analyze the data it is use SmartPLS 3.0 software application. The result of this research are: (1) Person-Job Fit is have significant impact on Job Satisfaction, (2) Person-Job Fit is have significant impact on Organizational Commitment, (3) Job Satisfaction is have significant impact on Organizational Commitment, (4) Person-Job Fit is not have significant impact toward Organizational Citizenship Behavior, (5) Job Satisfaction is have significant impact toward Organizational Citizenship Behavior, and (6) Organizational Commitment is not have significant impact toward Organizational Citizenship Behavior.